Grados días y crecimiento del fruto de genotipos foráneos de piñon (Jatropha curcas L.) en el valle del río Carrizal - Lucas Alcívar, Karen Pierina (2023)
Piñón is a crop that has become very important worldwide due to the quality of the oil produced by its seeds, with great potential for the production of biofuels. Currently, promising genetic material has been generated that must be evaluated in various environments in order to select those with the best growth and productive potential. Therefore, the objective of this research was to evaluate the accumulation of degree days and fruit growth rate in foreign genotypes of piñón under conditions of the Carrizal river valley. A randomized complete block design was used with a factorial arrangement of six genotypes (JAT 001100, JAT 001103, JAT 001164, JAT 001165, 041 and 052) and two seasons (dry and rainy), with 12 treatments and four replicates. The variables recorded were accumulation of degree days (AGD), growing time (TC), fruit diameter (DF), fruit length (LF) and fruit weight (PF). Data were analyzed by ANOVA and Tukey's test (p<0.05). AGD, TC, DF and LF were significantly influenced (p<0.05) by the seasons of the year, but not by genotypes and the respective interaction (p>0.05). During the rainy season, higher fruit growth was evidenced, but lower TC and AGD, in relation to the dry season, independently of the genotypes evaluated. It is concluded that it is necessary to continue evaluating fruit growth and AGD for several years and locations, in order to adjust data and have better selection criteria.